2010
DOI: 10.1007/s11262-010-0480-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection and subcellular localization of Mal de Río Cuarto virus P9-1 protein in infected plant and insect host cells

Abstract: Mal de Río Cuarto virus (MRCV), a member of the genus Fijivirus, family Reoviridae, has a genome consisting of 10 dsRNA segments. The segment 9 (S9) possesses two non-overlapping open reading frames (ORF-1 and ORF-2) encoding two putative proteins, MRCV P9-1 and MRCV P9-2, both of unknown function. The MRCV S9 ORF-1 was RT-PCR amplified, expressed in pET-15b vector, and the recombinant protein produced was used to raise an antiserum in rabbit. Western blot with the specific MRCV P9-1 antiserum detected a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…3), confirming the hypothesis that the viroplasm is the site for the replication and assembly of fijiviruses. Our results extend the limited information from previous electron microscopic studies that showed that P9-1 of two other fijiviruses (RBSDV and MRCV) exclusively localized in the matrix of viroplasms in virus-infected cells (9,12,19). With the evidence indicating that P9-1 alone was necessary for the formation of viroplasm-like structures in nonhost cells (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…3), confirming the hypothesis that the viroplasm is the site for the replication and assembly of fijiviruses. Our results extend the limited information from previous electron microscopic studies that showed that P9-1 of two other fijiviruses (RBSDV and MRCV) exclusively localized in the matrix of viroplasms in virus-infected cells (9,12,19). With the evidence indicating that P9-1 alone was necessary for the formation of viroplasm-like structures in nonhost cells (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Being highly homologous to RBSDV P9-1 (64.5% identity) [34], Mal de Rio Cuarto virus (MRCV) P9-1, which was detected in viroplams in both infected plants and planthoppers [35], was found to be sufficient for the formation of viral inclusion body (VIB)-like structures when expressed in Spodoptera frugiperda Sf9 cells [36]. There might be distinct mechanisms involved in viroplasm formation in insect and plant hosts.…”
Section: Discussionmentioning
confidence: 99%
“…P6 is also thought to self-interact and to form punctuate VLS in the cytoplasm and to recruit P9-1 [15]. It has ATPase activity and is associated with the formation of viroplasms [2,10]. The Mal de Rio Cuarto virus (MRCV) P9-1 can also self-interact and bind ssRNA.…”
mentioning
confidence: 99%